Komunikasi Organisasi dalam Meningkatkan Kinerja Pegawai pada Instansi Komisi Pemilihan Umum Kabupaten Badung - Sidantha, I Nyoman Windu Surya; Putrawan, I Nyoman Alit; Wiguna, I Made Arsa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2025)
Organizational communication is the process of exchanging information between members of an organization to achieve common goals and ensure effective operations. One of the organizations formed by the government to handle the election process is the General Election Commission (KPU). The objectives of this study are (1) Analyzing the implementation of organizational communication in improving employee performance in the Badung Regency KPU office after the 2020 Simultaneous Regional Elections; (2) Analyzing organizational communication obstacles in improving employee performance in the Badung Regency KPU agency after the implementation of the 2020 Simultaneous Regional Elections; (3) To find out the implications of organizational communication in improving employee performance in the Badung Regency KPU agency after the implementation of the 2020 Simultaneous Regional Elections. The data collection techniques used in this study are by using observation, interviews, documentation, and triangulation. qualitative descriptive methods analyze the results of the data. The results of this study are (1) the General Election Commission (KPU) of Badung Regency applies the concept of organizational communication and applies several concepts of organizational communication and performance concepts; (2) Communication obstacles faced, namely framework obstacles and technical obstacles; (3) Implications obtained by the Badung Regency General Election Commission, namely: (a) Implications for improving employee performance; (b) Implications of internal human resources. Theoretically, this research makes a significant contribution to the development of communication science, especially in the realm of organizational communication, by showing how effective communication implementation can encourage improvement in institutional performance after major political agendas such as the Regional Elections.